Confluences in the training of educators in the areas of Natural Sciences and Languages from the Social Technology of earth paint (Práxis Educativa, 2023)
This work discusses the Agroecology potential as a point of confluence and mobilization between different knowledge and practices in different educational contexts, especially in teaching degrees. For this, it starts from the analysis of a pedagogical event involving different undergraduate classes in different qualifications: Biological Sciences and Rural Education in Natural Sciences and in Languages and Codes. From a theoretical point of view, it is proposed the exercise of articulating references from different scientific communities, focusing on prioritizing dialogic and ecological postures. The reflections presented aim to contribute to a broader debate on emancipatory, sustainable and cooperative pedagogical practices, which are understood here as important in citizenship education both in rural and urban schools.Keywords: Agroecology. Ecology of practices. Dialogic education.